Konsep Ulama dalam Pandangan Mufassir Indonesia: Studi Aspek-aspek Keindonesiaan dan Metodologi Tafsir al-Azhar Karya Hamka dan Penafsirannya terhadap Term “Ulama” dalam al-Qur’an - Muhammad Fatih (PROGRESSA: Journal of Islamic Religious Instruction, 2019)
Hamka is one of Indonesia's most productive scholars. His work is no less than 85 titles in various fields of science. One of them is Tafsir Al-Qur'an 30 juz named Tafsir al-Azhar. His role as an ulama was evidenced, among others, by his organizational position as Chairman of the Indonesian Ulema Council (MUI) in 1975-1981, and the honorary Doctorate Award from the Al-Azhar University, Cairo, and Kebangsaan University, Malaysia. His work as a national figure is also evident in a series of activities he does. His expertise and expertise in the field of literature certainly gives its own influence and color in the works he wrote, not least in his Tafsir book. Hamka's capacity as an ulema of the archipelago, Muhammadiyah's missionary figure, chairman of the Indonesian Ulema Council, his love for the country and the struggle he undertook certainly gave a special color in interpreting the Qur'an, including his views on the concept of Ulama. In Al-Azhar's Tafsir, Indonesian nuances and specific phenomena of the Archipelago are evident, which represent the breadth of knowledge and rich experience, love and pride towards the Indonesian people, and their firmness in interpreting the concept of Ulama